An Integrated Bioarchaeological Approach to the Medieval 'Agricultural Revolution': A Case Study from Stafford, England, c.ad 800–1200. (November 2020) - Hamerow, Helena; Bogaard, Amy; Charles, Michael; Forster, Emily; Holmes, Matilda; McKerracher, Mark; Neil, Samantha; Ramsey, Christopher Bronk; Stroud, Elizabeth; Thomas, Richard
Abstract : In much of Europe, the advent of low-input cereal farming regimes between c. ad 800 and 1200 enabled landowners—lords—to amass wealth by greatly expanding the amount of land under cultivation and exploiting the labour of others. Scientific analysis of plant remains and animal bones from archaeological contexts is generating the first direct evidence for the development of such low-input regimes. This article outlines the methods used by the FeedSax project to resolve key questions regarding the 'cerealization' of the medieval countryside and presents preliminary results using the town of Stafford as a worked example. These indicate an increase in the scale of cultivation in the Mid-Saxon period, while the Late Saxon period saw a shift to a low-input cultivation regime and probably an expansion onto heavier soils. Crop rotation appears to have been practised from at least the mid-tenth century.